Optical coherence tomography assessment of the mechanistic effects of rotational and orbital atherectomy in severely calcified coronary lesions. Issue 6 (11th May 2015) - Kini, Annapoorna S.; Vengrenyuk, Yuliya; Pena, Jacobo; Motoyama, Sadako; Feig, Jonathan E.; Meelu, Omar A.; Rajamanickam, Anitha; Bhat, Arjun M.; Panwar, Sadik; Baber, Usman; Sharma, Samin K.
Abstract : Objectives: This study sought to assess the mechanistic effect of rotational atherectomy (RA) and orbital atherectomy (OA) on heavily calcified coronary lesions and subsequent stent placement using optical coherence tomography (OCT). Background: RA and OA are two main approaches to ablate coronary calcium. While small case reports have described the mechanistic effect of RA in calcified coronary lesions, there has been no imaging study to assess the effect of OA on coronary artery architecture and/or compare the effects of two atherectomy devices. Methods: This study analyzed 20 consecutive patients with OCT imaging performed after atherectomy and after stent implantation, RA ( n  = 10) and OA ( n  = 10). Results: Postatherectomy OCT analysis identified tissue modification with deep dissections in around a third of lesions after RA and OA; however, post OA dissections ("lacunae") were significantly deeper (1.14 vs. 0.82 mm, P  = 0.048). Post OA/RA lesions with dissections had significantly higher percentage of lipid rich plaques and smaller calcification arcs as compared to plaques without dissections. Stents after OA were associated with a significantly lower percent of stent strut malapposition than post RA stents (4.36 vs. 8.02%, P  = 0.038). Conclusions: Although the incidence of dissections was comparable between RA and OA cases, OA resulted in deeper tissue modifications (lacunae) as shown by OCT imaging. The finding might provide an explanation for a better stent apposition after OA as compared to RA. Their impact on long‐term outcome needs to be determined. © 2015 Wiley Periodicals, Inc.